ACCOUNTABILITY AND TRANSPARENCY OF WAQF MANAGERS IN INCREASING TRUST IN ENDOWMENTS FOR DEVELOPMENT: LITERATURE STUDY - Selfi Afriani Gultom; Andri Soemitra (Jurnal Akuntansi dan Pajak, 2022)
This article analyzes the role of accountability and transparency in increasing the trust of waqf institutions. Along with the development of information and science, waqf has become a financial instrument that is not only a means of improving welfare but also a supporter of development that can create state progress. This article is a literature study of reputable national and international books, journals. The discussion is sorted by taking content that is in accordance with the focus of the accountability theme. There are 50 selected journals with 20 national journals and 30 international journals. Furthermore, the content is divided into six focus discussions. The results of the discussion found that accountability and transparency were the main indicators to increase the trust of the wakif and the public regarding the waqf funds entrusted to the waqf management institution. Accountability and transparency are carried out not just preparing waqf accountability reports according to standards. Reports must be informed massively to all wakif, stakeholders, and the public by using various communication media, both print, and electronic media, so that waqf becomes a culture. The integrity of information will increase trust, increase the number of wakif and funds, add models of waqf instruments that can be used for comprehensive community development for the development of the country.